Experimental and computational fluid dynamics investigations of tracking CPC solar collectors. (15th March 2020) - Yuan, Guofeng; Fan, Jianhua; Kong, Weiqing; Furbo, Simon; Perers, Bengt; Sallaberry, Fabienne
Highlights: Collector efficiency of a tracking CPC solar collector measured. Distribution of solar irradiance on receiver tube surface determined by means of ray tracing. A simplified CFD model of the CPC solar collector developed and validated. Collector efficiencies at higher temperatures of 100 °C and 130 °C predicted by the CFD model. Influence of ETFE foil on collector efficiency elucidated. Abstract: The aim of the paper was to investigate thermal performance of two newly developed 15.4 m 2 compound parabolic concentrator (CPC) solar collectors both theoretically and experimentally. The two collectors are identical except that one collector is equipped with a transparent Ethylene tetrafluoroethylene (ETFE) foil and the other collector is not. Experimentally the solar collectors were tested in an outdoor test facility at different temperatures. Collector efficiencies were determined. Theoretically simplified CFD models of the CPC solar collectors were developed and validated against the measurements. A ray tracing tool Tonatiuh was used to calculate distribution of solar irradiance on the receiver. The influence of the ETFE foil on collector heat loss coefficient and efficiency was investigated. The results show that the CFD model predicts satisfactorily temperature rises of the collectors in the temperature range between 20 °C and 81 °C. The deviations between the measured and the calculated temperature rises were limited to ±0.3 K with a relative error less than 3.7%. By installation of the ETFE foil, the first order collector heat loss coefficient decreased from 1.42 to 0.82 W/m 2 /K. Efficiency of the collector with the ETFE foil was measured to be 63%, 55% and 54% for a mean collector fluid temperature of 27 °C, 63 °C and 81 °C respectively. For a solar irradiance of 895 W/m 2 and a mean collector temperature of 133 °C, collector efficiency is predicted to increase from 36% to 41% by installation of the ETFE foil. Another 5% increase of collector efficiency is expected if installation of the foil is made airtight.